Structure for Knowledge Creation in Nepalese Hospitality Industry (PYC Nepal Journal of Management, 2018)
This paper examines the different factors promoting structure for knowledge creation in the business enterprises of sectors such as hotel, travel and trekking agencies. The survey was conducted in the month of May, 2015 in Kathmandu valley. The totals of 382 responses were taken for analysis. The total response rate was 83 per cent. Self-administered questionnaires were used to collect the perceptive opinions from the respondents. The study concludes that the majority of employees of the hospitality industry do not need to refer to someone else in decision making processes and have to perform many activities that are not covered by some formal procedures.